Islamic University Sulthan Thaha Saifuddin Jambi: A Beacon of Change in Enhancing the Quality of Inclusive Private Islamic Higher Education - Norainun Norainun; Maisah Maisah; Siti Marpuah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to analyze the institutional conditions, leadership challenges, and strategic efforts of the State Islamic University Sulthan Thaha Saifuddin Jambi in improving the quality of inclusive private Islamic higher education institutions in Jambi Province to support sustainable academic and institutional development. Methodology: This study employed a qualitative phenomenological approach using a purposive sampling technique to select key academic leaders and stakeholders from Kopertais Region XII Jambi, including rectors, vice rectors, and heads of Islamic higher education institutions. Data were collected through in-depth interviews, document analysis, and observation, then analyzed using Creswell’s phenomenological framework reduction, horizontalization, clustering, and synthesis with triangulation ensuring validity and reliability of findings. Main Findings: The State Islamic University Sulthan Thaha Saifuddin Jambi achieved significant progress in accreditation, faculty development, and institutional transformation, serving as a model for inclusive private Islamic higher education. Findings reveal internal and external leadership barriers, including limited motivation, time, and collaboration. Leaders implemented strategies such as digital-based management, human resource development, and continuous mentoring to enhance institutional quality. Novelty/Originality of this study: This study introduces a new perspective by integrating institutional transformation, leadership challenges, and strategic digital-based management within the framework of Kopertais Region XII. It advances existing knowledge by presenting the State Islamic University Sulthan Thaha Saifuddin Jambi as a replicable model for improving the quality and inclusivity of private Islamic higher education in Indonesia.